Impact Analysis of the Subscale of Aggression in Depression and Anxiety, Among Adolescents Aged 16-18 Years- Case Study: High Secondary School ‘’Luciano Motroni’’ Prizren - Rizanaj, Nderim (European Journal of Multidisciplinary Studies, 2021)
Aggression is a phenomenon that encompasses some very significant subscales and can be manifested through aggressive behaviors, hostility to friends, anger, uncontrolled / inconsistent reactions, and verbal and indirect aggression. These factors need to be carefully considered and followed up with research in order to give young people room to improve behaviors and achieve high achievement, otherwise it can affect adolescent anxiety and depression. The purpose of this study is to analyze the effects of underlying aggression such as anger, hostility, verbal aggression, indirect aggression, inconsistent response to anxiety, and depression in adolescents aged 16-18. This study included three groups of students, 16 years old, 17 years old and 18 years old, with 50 adolescents in each group, so the total sample is 150 adolescents aged 16-18 years. The research belongs to the quantitative type and the case study was selected ’Luciano Motroni’ High Secondary School in Prizren municipality during January 2020. Research results show that depression scales such as verbal aggression have an impact on anxiety and depression (rho = .163 *, p value = .047), anger (rho = .385 **, p value = .000), hostility (rho = .174 *, p value = .033), indirect aggression (rho = .261 **, p value = 001), and inconsistent response (rho = .170 *, p value = .037) which are statistically significant at 1 % and 5% confidence level. Compared to a research conducted in 2019, entitled ’’ Association between anxiety and aggression in adolescents: a cross-sectional study ’’ we see that aggression has a significant impact on youth anxiety. Thus, the subscales of aggression represent an important significant link in adolescent anxiety and depresion. Finally, we conclude that sub scales of aggression have a statistically significant impact on adolescent anxiety and depression among young people aged 16-18, in the municipality of Prizren. What we recommend is the training and support of young people during their secondary education journey.